2022
DOI: 10.1007/jhep05(2022)187
|View full text |Cite
|
Sign up to set email alerts
|

DUNE atmospheric neutrinos: Earth tomography

Abstract: In this paper we show that the DUNE experiment can measure the Earth’s density profile by analyzing atmospheric neutrino oscillations. The crucial feature that enables such measurement is the detailed event reconstruction capability of liquid argon time projection chambers. This allows for studying the sub-GeV atmospheric neutrino component, which bears a rich oscillation phenomenology, strongly dependent on the matter potential sourced by the Earth. We provide a pedagogical discussion of the MSW and parametri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…The impact of systematic uncertainties related to the oscillation parameters and to the normalization, shape and flavour content of the atmospheric neutrino flux have been discussed more extensively in some other recent studies, both for ORCA-like (Rott et al, 2015;Winter 2016;Bourret and Van Elewyck, 2019;Capozzi and Petcov, 2022;D'Olivo Saez et al, 2022) and DUNE-like (Kelly et al, 2022) detectors, and shown to have a limited to moderate impact on tomographic measurements. In the specific case of the measurement of the core composition which is our focus here, we benefit from the fact that such systematic effects can be mitigated and controlled by exploiting the sample of neutrino events that only traverse the mantle (and not the core).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of systematic uncertainties related to the oscillation parameters and to the normalization, shape and flavour content of the atmospheric neutrino flux have been discussed more extensively in some other recent studies, both for ORCA-like (Rott et al, 2015;Winter 2016;Bourret and Van Elewyck, 2019;Capozzi and Petcov, 2022;D'Olivo Saez et al, 2022) and DUNE-like (Kelly et al, 2022) detectors, and shown to have a limited to moderate impact on tomographic measurements. In the specific case of the measurement of the core composition which is our focus here, we benefit from the fact that such systematic effects can be mitigated and controlled by exploiting the sample of neutrino events that only traverse the mantle (and not the core).…”
Section: Discussionmentioning
confidence: 99%
“…The DUNE-like model (Abi et al, 2020a;2020c;Kelly et al, 2022) accounts for the superior resolution and reconstruction capabilities of the Liquid Argon detection technique, at the cost of a much smaller instrumented volume. At the other extreme, the ORCA-like model (Adrian-Martinez et al, 2016;Aiello et al, 2022) reflects the higher detection threshold and degraded reconstruction performances that result from a sparsely instrumented -although larger -volume.…”
Section: Sensitivity Of Upcoming Neutrino Detectors To the Outer Core...mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of probing the internal structure of Earth using these density-dependent matter effects is known as "neutrino oscillation tomography". These studies have been performed using man-made neutrino beams [61][62][63][64][65][66][67][68][69][70][71], supernova neutrinos [72,73], solar neutrinos [72,[74][75][76][77][78][79], and atmospheric neutrinos [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. In the sub-GeV and multi-GeV energy ranges, atmospheric neutrinos are the best source of neutrinos to probe the internal structure of Earth because they have access to a wide range of baselines starting from about 15 km to 12750 km which cover all the layers of Earth.…”
Section: Jhep04(2023)068mentioning
confidence: 99%
“…Beyond the MSW effect, at energies around 1 GeV, the oscillation is enhanced for some trajectories crossing Earth's core and mantle due to the matter distribution, the so-called parametric resonance [49,[138][139][140][141][142][143][144][145][146][147][148]. Both types of resonance happen for neutrinos if the mass ordering is normal and for anti-neutrinos ∆ 21 that goes to zero, so that δ CP has a larger impact in the neutrino evolution at sub-GeV energies and for Earth-size baselines.…”
Section: A Neutrino Evolution Through the Earthmentioning
confidence: 99%